Analisis de la regeneracion natural de Pinus pinaster Ait. en los arenales de Almazan-Bayubas (Soria, España) - Rodriguez garcia, E.=700 1 Juez, L.; Guerra, B.; Bravo, F.
(En, Es)
Ilus., 43 ref.
Keywords: PINUS PINASTER; CORTA; REGENERACION; METODOS ESTADISTICOS; ESPAÑA; DISEMINADO; ANALISIS MULTIVARIANTE